An high performance liquid chromatographic method for the quantification of cotinine in the urine of preschool children - (:unkn) unknown (GOVI-VERLAG PHARMAZEUTISCHER VERLAG GMBH, 2006)
Tobacco smoke exposure is an important and preventable cause of morbidity among children. Enviromental tobacco smoke (ETS) increases respiratory symptoms and disease and also decreases lung function in children who live in a household with at least one smoker. We have developed a simple and reliable HPLC method with diode array dedection to determine the urine concentrations of cotinine in children aged 3 to 6 years, exposed to ETS. The assay involved a liquid-liquid extraction with chloroform. The HPLC method utilized a Chromasil C-18 column (150mm x 4.6mm i.d.) and an isocratic mobile phase of phosphate buffer: acetonitrile (83:17 v/v, 0.02 M containing 0.1% triethylamine, adjusted to pH 6.72 with orthophosphoric acid), at a flow rate of 0.7 ml min(-1). The detection was performed at 260 nm and the total analysis time of analysis was less than 15 min. Linearity ranged from 0 to 80 mu g L-1; correlation coefficients (r(2)) for calibration curves were greater than 0.99. With 2 mL of urine for extraction, the limit of detection was 0.1 mu g L-1. The mean extraction ratio of cotinine was 88.78%. This analytical method is suitable for the determination of cotinine levels in a large number of urine samples.
Keywords: TOBACCO-SMOKE EXPOSURE; SOLID-PHASE EXTRACTION; HUMAN LIVER-MICROSOMES; PASSIVE SMOKING; C-OXIDATION; NICOTINE; PLASMA; GAS; RADIOIMMUNOASSAY; METABOLISM